Exploration of the Numerical Value of One in the Qur'an - Titania Ramadhani; Sugiatno Sugiatno; Agung Hartoyo; Fredi Ganda Putra (Pendidikan Matematika Universitas Muhammadiyah Bangka Belitung, 2022)
This article describes the exploration results of the verses of the Qur'an, which contain the concept of monotheism with a numerical value of one. This research started from learning number recognition in class, which still seemed monotonous. Furthermore, the limitations of teaching materials make integrating mathematics learning with Islamic science more difficult. Numbers have an important role in various aspects of life. Al-Qur'an, the main subject taught in Islamic schools, can be used as initial knowledge to support learning mathematics. Therefore, introducing numbers to students must be integrated with Islamic science, especially monotheism in learning at school, to lead students to successful learning and a change in religious awareness. The data collection techniques used are documents such as interpretations of the Qur'an, the Qur'an and their translations, articles, journals, books, or other literature related to mathematics and the Qur'an. The information in this study was derived from search and collection results obtained through the Ministry of Religion's Qur'an application, the Indonesian Qur'an application, and other data in the form of documents. Then, the data analysis technique used to get the numerical value of one in the Qur'an is the Miles & Huberman analysis method combined with Rodriguez modeling and